1999
DOI: 10.1103/physreve.60.1936
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced structural correlations accelerate diffusion in charge-stabilized colloidal suspensions

Abstract: Theoretical calculations for colloidal charge-stabilized suspensions and hard sphere suspensions show that hydrodynamic interactions yield a qualitatively different particle concentration dependence of the short-time self-diffusion coefficient. The effect, however, is numerically small and hardly accessible by conventional light scattering experiments.Applying multiple-scattering decorrelation equipment and a careful data analysis we show that the theoretical prediction for charged particles is in agreement wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…The coefficient a s ≈ 1.8 in the expression for the sedimentation coefficient is nearly constant. The present expressions for D r and D s have been confirmed experimentally [69,75], and we will show that they conform with existing LB and our ASD simulation data up to φ ≈ 0.35 and φ ≈ 0.1, respectively.…”
Section: Charge-stabilized Spheressupporting
confidence: 66%
“…The coefficient a s ≈ 1.8 in the expression for the sedimentation coefficient is nearly constant. The present expressions for D r and D s have been confirmed experimentally [69,75], and we will show that they conform with existing LB and our ASD simulation data up to φ ≈ 0.35 and φ ≈ 0.1, respectively.…”
Section: Charge-stabilized Spheressupporting
confidence: 66%
“…This allows the improvement of the δγ scheme by replacing the hard-sphere δγ prediction for D s by the accurate simulation value which is a less time-consuming method than the full ASD simulation of H(q). The hybrid method amounts to an upward shift of the δγ − H(q) by a small to moderately large value, since the D s of charged spheres is larger than that of neutral ones [11,21]. Even without the correction for D s , the δγ scheme is useful in detecting trends in the behavior of H(q).…”
Section: Simulation and Theorymentioning
confidence: 99%
“…(24) and (25) have recently been confirmed by lattice Boltzmann simulations, 36 DDLS, 58 and DLS. 59 It was shown that eqn. (24) applies up to f % 0.3, whereas eqn.…”
Section: Sed Scaling In Binary Hard-sphere Mixturesmentioning
confidence: 99%